Regulation of E-Government Development in Manado City - Carlo Adrin Gerungan; Marthin Luther Lambonan; Mario A. Gerungan (Journal of General Education and Humanities, 2026)
This study aims to analyze the regulatory framework governing the development of E-Government in Manado City. By combining a normative juridical approach with an empirical approach, the research provides a comprehensive understanding of both the legal basis and practical implementation of digital-based governance. The normative juridical approach examines the regulations that serve as the foundation for E-Government administration, while the empirical approach observes their application in practice. Data were collected in Manado City over two months through interviews, observations, and analysis of secondary sources, including official documents and relevant literature. Qualitative descriptive analysis, involving data reduction, presentation, and conclusion drawing, was used to process the information. The findings indicate that E-Government in Manado City has advanced through the integration of various digital services to enhance public service quality. However, implementation remains suboptimal due to technical limitations in certain applications and gaps in human resource competencies. From a regulatory standpoint, the Manado City Government has established a solid legal foundation through Mayor Regulation Number 10 of 2018 and Mayor Regulation Number 31 of 2022, which guide the development and implementation of the Electronic-Based Government System. The study highlights that the effectiveness of E-Government depends on continuous support, including capacity building for human resources, strengthened digital infrastructure, enhanced cybersecurity, and periodic regulatory updates. Sustained efforts in these areas are essential to achieving modern, efficient, and responsive governance that effectively serves the community’s needs.